1356 [compact disc, unabridged] : a novel - Cornwell, Bernard (Cornwell, Bernard. Grail quest., 2013)
On September 19, 1356, a severely outnumbered English army faced off against the French at the Battle of Poitiers. But what seemed like certain defeat became instead the most decisive English victory of the Hundred Years' War.